Heterozygous Polg mutation causes motor dysfunction due to mtDNA deletions. (22nd October 2014) - Fuke, Satoshi; Kametani, Mizue; Yamada, Kazuyuki; Kasahara, Takaoki; Kubota‐Sakashita, Mie; Kujoth, Gregory C.; Prolla, Tomas A.; Hitoshi, Seiji; Kato, Tadafumi
Abstract Objective Mutations in nuclear‐encoded mitochondrial DNA (mtDNA) polymerase (POLG) are known to cause autosomal dominant chronic progressive external ophthalmoplegia (adCPEO) with accumulation of multiple mtDNA deletions in muscles. However, no animal model with a heterozygous Polg mutation representing mtDNA impairment and symptoms of CPEO has been established. To understand the pathogenic mechanism of CPEO, it is important to determine the age dependency and tissue specificity of mtDNA impairment resulting from a heterozygous mutation in the Polg gene in an animal model. Methods We assessed behavioral phenotypes, tissue‐specific accumulation of mtDNA deletions, and its age dependency in heterozygous PolgD257A knock‐in mice carrying a proofreading‐deficient mutation in the Polg. Results Heterozygous PolgD257A knock‐in mice exhibited motor dysfunction in a rotarod test. Polg+/D257A mice had significant accumulation of multiple mtDNA deletions, but did not show significant accumulation of point mutations or mtDNA depletion in the brain. While mtDNA deletions increased in an age‐dependent manner regardless of the tissue even in Polg+/+ mice, the age‐dependent accumulation of mtDNA deletions was enhanced in muscles and in the brain of Polg+/D257A mice. Interpretation Heterozygous PolgD257A knock‐in mice showed tissue‐specific, age‐dependent accumulation of multiple mtDNA deletions in muscles and the brain which was likely to result in neuromuscular symptoms. Polg+/D257A mice may be used as an animal model of adCPEO associated with impaired mtDNA maintenance.